Redesain Gedung Flat dosen muda Blok-N11 ITS Surabaya Dengan Mempertimbangkan Aspek Green Building PERMEN-PUPR 2021 - Fanani, Ahmad Rudi (Universitas Negeri Surabaya, 2023)
Buildings have a big enough role in increasing the effect of global warming. Research shows that building designs that use glass as a building envelope material can have a significant impact on the greenhouse effect. Therefore, it is important to apply the concept of green building to create a healthy and efficient environment. The design of the building with a green building concept also aims to reduce the impact of global warming. In PERMEN-PUPR 2021 it has been determined that there are 3 levels of achievement of a Green Building (BGH) including BGH Pratama, BGH Intermediate, and BGH Utama. This study aims to redesign the ITS Young Lecturer Flat Building which is located on Jalan Teknik Kesehatan Blok-N11 Surabaya from those that have not yet achieved a rating with a point acquisition of 42.4% to a BGH Pratama rating of 58.7% points as stipulated by PERMEN. - PUPR 2021. The results of this study are working drawings including floor plans, foundations, sloofs, beams, columns, floor plates, roof plans, building sections, and visible drawings. To achieve the BGH Pratama rating on the results of this redesign, it is necessary to redesign including adding green open space plan areas, adding vegetation crowns, adding smoking prohibition signs, selecting sanitary equipment, and adjusting the lighting needs of each room.